2020
DOI: 10.7150/ijms.47405
|View full text |Cite
|
Sign up to set email alerts
|

Lnc-MAP6-1:3 knockdown inhibits osteosarcoma progression by modulating Bax/Bcl-2 and Wnt/β-catenin pathways

Abstract: Osteosarcoma (OS) is the most common type of malignant bone tumor that affects children and adolescents. Still, the cellular and molecular mechanisms driving the development of this disease remain poorly understood. In this study, numerous dysregulated lncRNAs were identified by RNA-seq. As a result, we were able to find a novel lncRNA Lnc-MAP6-1:3 which is highly expressed in osteosarcoma. Using a set of approaches including gene knockdown, RT-PCR, oncogenic function assay and western blotting, we observed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Network pharmacological analysis implied that the molecular mechanism of the anti-MI/RI effect of DAD might be associated with apoptosis. The mammalian BCL-2 family member Bcl-2 was an anti-apoptotic protein, while Bax protein induced apoptosis by enhancing cytochrome c (Cyt-C) release from the mitochondria ( Aamazadeh et al, 2020 ; Lin et al, 2020 ). Therefore, the two targets of Bax and Bcl2 (Bax and Bcl2 belonged to the targets of DAD in anti-MI/RI) were validated in vitro .…”
Section: Resultsmentioning
confidence: 99%
“…Network pharmacological analysis implied that the molecular mechanism of the anti-MI/RI effect of DAD might be associated with apoptosis. The mammalian BCL-2 family member Bcl-2 was an anti-apoptotic protein, while Bax protein induced apoptosis by enhancing cytochrome c (Cyt-C) release from the mitochondria ( Aamazadeh et al, 2020 ; Lin et al, 2020 ). Therefore, the two targets of Bax and Bcl2 (Bax and Bcl2 belonged to the targets of DAD in anti-MI/RI) were validated in vitro .…”
Section: Resultsmentioning
confidence: 99%
“…The antiapoptotic protein Bcl-2, mainly located in the outer membrane of the mitochondria, was upregulated in osteosarcoma to inhibit the apoptosis induced by various stimuli, injury, and cell survival signals ( Valentin et al, 2018 ). Bax is an important pro-apoptotic gene ( Lin et al, 2020 ). When overexpressed, Bax can bind to homologous dimers and promote apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Elucidation of the molecular basis on which lncRNAs affect OS development and progression is essential to establish better treatment options [1,28]. Recently, lncRNAs have been identified that participate in OS progression, including cancerous cell growth, metastasis, and apoptosis [29][30][31]. LncRNA GNAS-AS1 was an important gene related to the formation and progression of nasopharyngeal carcinoma and breast cancer [17,18].…”
Section: Discussionmentioning
confidence: 99%